Mazhab dan Aliran Sosiologi Hukum: Perspektif Teoretis dan Relevansinya dalam Kajian Hukum Kontemporer - Ratri Pramudita; Enggy Yose; Hendi Efrianto Harianja; Nayla Azizah; Yuninda Fikri; Mutiara Putri Syahrani; Febra Anjar Kusuma; Susilo Susilo (Indo Publishing, 2026)
The sociology of law as a scientific discipline has developed through various schools and currents of thought that offer diverse theoretical perspectives on the relationship between law and society. This study aims to analyze the main schools and currents in the sociology of law, including the positivist school, the sociological jurisprudence school, the critical legal studies school, and the feminist legal theory school, as well as their relevance to contemporary legal studies. Using a normative-empirical legal research method with a conceptual and comparative approach, this study finds that each school offers a unique contribution to understanding the dynamics of law in social life. The positivist school emphasizes the autonomy and certainty of law, while the sociological jurisprudence school bridges formal law and social reality. Critical legal studies question the neutrality of law, and feminist legal theory reveals gender biases in the legal system. In the context of contemporary legal studies in Indonesia, the integration of these schools is relevant for overcoming the limitations of a purely normative approach and producing law that is more responsive to social needs and justice.